The wicked problem of B(A)ME degree award gaps and systemic racism in our universities - Ugiagbe-Green, Iwi; Ernsting, Freya (Frontiers in Sociology, 2022)
The independent regulator for higher education in England, the Office for Students (OfS), set new national targets in late 2018 to achieve equality of opportunity in higher education by tackling degree award gaps. The sector response to this was to measure degree award gaps between B(A)ME students and white students in their higher education institutions. Analysis of degree award gaps using quantitative methods has revealed an “unexplained gap”. We argue that the existence of this “unexplained gap” is evidence of “systemic racism”. However, the factors influencing a degree award and their associated gaps across different racialized groups of students are so complex, that its problematisation, never-mind its solution is inherently complex. It is our view, therefore, racialized degree award gaps are a wicked problem. Despite this, it is also our view that it is an important social justice endeavor that we must still seek to address as a sector. To do so, we propose a mixed methods approach that uses dynamic centring and an intersectional lens to better understand the experiences of racialized students within the higher education “system”. Current quantitative analysis of degree award gaps simply tells us how different groups of racialized students experience the system. In using a mixed methods approach in the way we outline, we may better understand the racialized lived experience of our students and the factors influencing the experience of different racialized groups within the “system”. This solution-focused approach can help create opportunities that enable students to better navigate social structures and systems and improve their experience in the system. However, this will not address the wicked problem of degree award gaps itself, which is complex, pervasive, and messy.